2022
DOI: 10.3389/fgene.2021.746665
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Association Study of Beef Traits in Local Alpine Breed Reveals the Diversity of the Pathways Involved and the Role of Time Stratification

Abstract: Knowledge of the genetic architecture of key growth and beef traits in livestock species has greatly improved worldwide thanks to genome-wide association studies (GWAS), which allow to link target phenotypes to Single Nucleotide Polymorphisms (SNPs) across the genome. Local dual-purpose breeds have rarely been the focus of such studies; recently, however, their value as a possible alternative to intensively farmed breeds has become clear, especially for their greater adaptability to environmental change and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 101 publications
2
8
0
Order By: Relevance
“…It is possible to observe a few clusters in the genomic relationship matrix ( Figure 3 ); however, they are not as straightforward as in SIM. We, therefore, can note that no population structure is present in Rendena breed (i.e., no subpopulations), which is in line with previous research ( Mancin et al, 2022 ). Only 633 eigenvalues explained 98% of G variance; thus, the scenario was closer to SIM2 than SIM1.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…It is possible to observe a few clusters in the genomic relationship matrix ( Figure 3 ); however, they are not as straightforward as in SIM. We, therefore, can note that no population structure is present in Rendena breed (i.e., no subpopulations), which is in line with previous research ( Mancin et al, 2022 ). Only 633 eigenvalues explained 98% of G variance; thus, the scenario was closer to SIM2 than SIM1.…”
Section: Resultssupporting
confidence: 91%
“…Only 633 eigenvalues explained 98% of G variance; thus, the scenario was closer to SIM2 than SIM1. In addition, we observed an average LD of 0.187 ± 0.107 per chromosome ( Mancin et al, 2022 ).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…In a study performed on the Rendena cattle bred in the Italian Alps important for beef production, it was found that SLC12A1, CGNL1, PRTG genes were associated with average daily body weight gain, LOC513941 gene was associated with carcass yield, CDC155 gene was associated with the content of boneless meat in the carcass, NLRP2 gene was associated with both indicators of carcass quality. Metabolic pathways analysis showed that some of the genes were associated with neurogenesis and synaptic signaling in cells, and some were associated with actin synthesis and transmembrane transport [30].…”
Section: Resultsmentioning
confidence: 99%